URGENSI PENGATURAN CYBERBULLYING TERHADAPANAK DALAM HUKUM POSITIF DI INDONESIA - Elfrida Firdausy Nuzula, (2022)
Cyberbullying crimes in the past year have increased. Meanwhile, positive rules or laws in Indonesia have not explicitly and explicitly regulated cyberbullying against children. The purpose of this study was to determine the urgency of regulating cyberbullying against children in positive law in Indonesia and to determine the prevention and handling of cyberbullying against children by the Indonesian Child Protection Commission (KPAI). This research is normative legal research that is equipped with interviews. The problem approach used is a statutory approach and a conceptual approach. The data sources are Primary Legal Materials, Secondary Legal Materials and Tertiary Legal Materials. Method of Data Collection by Studying the literature in which the researcher conducts a documentation study of secondary data and conducts interviews with resource persons consisting of academics, practitioners and KPAI. Data analysis techniques are qualitative, descriptive analytical presentation techniques. This study uses the method of finding the law of grammatical interpretation. The results of the study show that in order to provide a sense of security to children who are the successors of this nation, it is very important to have clear and explicit rules regarding the definition of bullying in the Child Protection Act. Regarding the rules of cyberbullying, according to researchers, ideally if it is made one between Article 27 paragraphs (1), (3), (4) with Article 29 of the ITE Law, as well as regarding the criminal threat. Then to complete the rules regarding cyberbullying, the definition of cyberbullying can be added including other aspects in it. Regarding the prevention and handling carried out by KPAI on cases of cyberbullying against children, it is appropriate. However, it may be added by collaborating between KPAI and other ministries or institutions or organizations.